2012
DOI: 10.6001/actamedica.v19i2.2313
|View full text |Cite
|
Sign up to set email alerts
|

Surface markers distinguishing mesenchymal stem cells from fibroblasts

Abstract: Human mesenchymal stem cells (MSCs) are widely used for treatment of various diseases. Clinical applications require large quantities of MSCs, therefore these cells must be expanded in the culture system. It is believed that contamination of MSC cultures with fibroblasts may lead to the decrease of the stem cell differentiation potential. Moreover, such stem cell preparations are potentially unsafe to use for clinical applications since a few fibroblasts can become tumorigenic. Therefore, there is a need to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 19 publications
(23 reference statements)
2
35
1
1
Order By: Relevance
“…This makes it impossible to use these markers to label stem cells in vivo. This is also supported by previous studies which showed that lung fibroblasts also expressed CD44, CD73, and CD105 [39][40][41]. Other articles showed that the expression of these markers were defined operationally only aiming at enriching cells that were clonogenic/multi-potent in vitro, and none of them appeared to participate directly in the molecular processes regulating selfrenewal versus differentiation [42,43].…”
Section: Limitations Of This Studysupporting
confidence: 64%
“…This makes it impossible to use these markers to label stem cells in vivo. This is also supported by previous studies which showed that lung fibroblasts also expressed CD44, CD73, and CD105 [39][40][41]. Other articles showed that the expression of these markers were defined operationally only aiming at enriching cells that were clonogenic/multi-potent in vitro, and none of them appeared to participate directly in the molecular processes regulating selfrenewal versus differentiation [42,43].…”
Section: Limitations Of This Studysupporting
confidence: 64%
“…The CD106 surface marker was reported positive in MSCs and negative in fibroblasts. On the other hand, strong positive expression (above 95%) of CD10 was described in fibroblasts and lower than 35% in MSCs (Cappellesso‐Fleury et al, ; Halfon et al, ; Kundrotas, ). In our study, however, DSCs, ASCs, and fibroblasts displayed variable expression of CD10 and were negative to CD106.…”
Section: Discussionmentioning
confidence: 99%
“…The third mesenchymal marker CD73 was more expressed in BCC than in margins and normal tissue. As the presence of CD90 and CD44 markers has been reported in basal cells and hair follicle stem cells (HFSCs) isolated from human skin, the discrimination between CSC and non‐neoplastic cells becomes more challenging …”
Section: Discussionmentioning
confidence: 99%